Postoperative Analgesic Effects of Quadratus Lumborum Block Versus Transversus Abdominis Plane Block in Pediatric Lower Abdominal Surgeries: A Systematic Review and Meta-Analysis - Aldalati AY; Hussein AM; Ataya R; Alrabadi B; Odat RM; Idrees M; Al-dabagh A; Kamal Z; Aloudat O; Al-qaoud A (Journal of Pain Research)
Abdullah Yousef Aldalati,1 Ayham Mohammad Hussein,2 Raghad Ataya,1 Bassel Alrabadi,1 Ramez M Odat,1 Muhammad Idrees,3 Ahmad Al-dabagh,4 Zaid Kamal,5 Osama Aloudat,6 Ahmad Al-qaoud7 1Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Faculty of Medicine, Al-Balqa’ Applied University, Salt, Jordan; 3Lahore General Hospital, Lahore, Punjab, Pakistan; 4Faculty of Medicine, Sana’a University, Sana’a, Yemen; 5Department of General Surgery, Advent Health Medical Group, Tampa FL, USA; 6Department of Pediatrics of Saint Louis University School of Medicine, SSM Health Cardinal Glennon Children’s Hospital, St. Louis, MO, USA; 7Department of General Anesthesia, NYCHHC Metropolitan Hospital, New York, NY, USACorrespondence: Ahmad Al-dabagh, Department of Medicine, Sana’a University, Wadi Dhaher Road, P.O. Box 13078, Sana’a, Yemen, Email ahmadaldabagh4@gmail.comObjective: Management of postoperative pain in pediatric patients is challenging. Traditional methods of postoperative pain management may not always provide adequate relief. We aim to compare the effect of Quadratus Lumborum Block (QLB) and Transversus Abdominis Plane Block (TAPB) on the quality of postoperative analgesia in pediatrics undergoing lower abdominal surgeries.Methods: We systematically searched PubMed, Scopus, Web of Science, and Cochrane Library up to August 2024 for studies that compared QLB and TAPB in the context of pediatric lower abdominal surgery. Pooled mean difference (MD), standardized mean difference (SMD), and odds ratio (OR) were calculated by a random effect model using RevMan 5.4.Results: Nine studies met the pre-defined inclusion criteria. Pooled analysis indicated that postoperative pain measured by the FLACC score was lower in the QLB group compared to the TAPB group (MD: − 0.37; 95% CI: − 0.51, − 0.23; P < 0.00001). QLB was also associated with lower rescue analgesic demand (OR: 0.25; 95% CI, 0.13, 0.49; P < 0.0001), higher parent satisfaction (SMD: 0.78; 95% CI: 0.53, 1.02; P < 0.00001), longer time without the need for analgesic administration (MD: 1.04; 95% CI: 0.38, 1.71; P = 0.002), and lower paracetamol consumption (SMD: − 1.40; 95% CI: − 2.43, − 0.36; P = 0.008). However, no significant difference was found in terms of postoperative nausea, vomiting, and heart rate.Conclusion: QLB provides superior analgesia compared to TAPB in pediatrics undergoing lower abdominal surgeries. Keywords: QL block, TAP block, pediatric, abdominal surgeries, meta-analysis